Stopping pollution - Chambers, Catherine (Chicago, Ill Heinemann Library, 2009)
People around the world are suffering from pollution. This book looks at some of these issues like exhaust emissions and the chemical chaos on our farms
Environment
Keywords: Pollution prevention; Pollution